Excavating a Mid-Iron Age crouched inhumation on the shores of Loch Gruinart, Islay, Argyll and Bute. Issue 1 (March 2019) - Hawthorne, Donna; Paton, Kevin
Abstract : Human remains uncovered across Atlantic Scotland have displayed a variety of burial rites practised throughout the Iron Age. An excavation on the island of Islay, as part of the Historic Environment Scotland Human Remains Call-Off Contract, has uncovered a crouched inhumation eroding out of sand dunes near the western shore of Loch Gruinart. Osteological analysis of the skeleton revealed it is that of an adult male, aged between 26 and 35 years. The body was found in a crouched position on its left-hand side, aligned south-east to north-west, with the head raised up and turned to face the west. No artefacts or grave goods were found in association with the burial. Radiocarbon dating has established that the remains relate to the Mid-Iron Age. The evidence uncovered here adds to the evolving narrative of the nature and date of the varying burial rites practised throughout this region during the Iron Age.